Volume 3: Design and Analysis 2008
DOI: 10.1115/pvp2008-61789
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Deformation and Fatigue Behaviors of Stainless Steel 304L Including Mean Stress and Pre-Straining Effects

Abstract: This paper discusses cyclic deformation and fatigue behavior of three grades of stainless steel 304L. Effects of pre-straining and mean stress were investigated and it was observed that these parameters influence both deformation and fatigue behaviors. At HCF, significant secondary hardening was observed for two of the materials, leading to a significant change in fatigue behavior at long lives. For two of the materials, pre-strained tests were also conducted. Hardening was observed as a consequence of pre-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The benefits of residual compressive stresses to enhance the fatigue resistance of traditional metallic components have long been recognized (Ref [27][28][29]. For example, many engineering components have been shot-peened or cold-worked with fatigue strength enhancement as the primary objective.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of residual compressive stresses to enhance the fatigue resistance of traditional metallic components have long been recognized (Ref [27][28][29]. For example, many engineering components have been shot-peened or cold-worked with fatigue strength enhancement as the primary objective.…”
Section: Discussionmentioning
confidence: 99%
“…Following earlier work [18], SCH is also observed in copper and is considered as a general phenomenon which occurs in f.c.c materials at high-cycle fatigue behavior. A previous study [19] on two grades (THYSSEN and CLI) of 304L stainless steel has shown that fatigue life is much longer when SCH occurs but no correlation is found between the emergence of this phenomenon and the fatigue life.…”
Section: Analyses and Discussionmentioning
confidence: 87%
“…To take into account the LWR environment effect, we consider the approach based on the environmental factor F en that we apply on the SWT-life curve. Since F en is defined as F en = N f,air N f,water (8) and since it is a constant for a given testing condition (T, .…”
Section: Discussionmentioning
confidence: 99%
“…The tested material was a laminated plate made of AISI 304L stainless steel manufactured by Creusot-Loire Industrie (sheet XY182), annealed at 1100 • C and quenched with water. This material has been used in various previous studies [7,8,10,21]. The mechanical properties and chemical composition are presented in Tables 1 and 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation